Data-Centric Business and Applications Advancements in Information and Knowledge Management, Volume 2 - Štarchoň, Peter; Fedushko, Solomiia; Gubíniová, Katarína (Lecture Notes on Data Engineering and Communications Technologies, 2024)
X, 441 p. 106 illus., 92 illus. in color.